An Analysis of Declarative and Interrogative Sentences In “Don’t Look Up” Movie - Agustinus Fransiskus; Widi Syahtia Pane; Godefridus Bali Geroda (Wadah Inovasi Indonesia, 2023)
AbstractBackground:Human communicate by using sentences in daily life. There are two types pf sentences usually used by people in an utterance declarative and interrogative sentence and it is important to know the meaning for every structure of sentences in order to avoid misunderstand between people. This study aims to analyze types and deep structure of Declarative and Interrogative sentences that appeared in “Don’t Look Up” MovieMethodology: The researcher used a design for content analysis. The characters shown in the film